Accelerating the development of phase‐change random access memory with in‐fab plasma profiling time‐of‐flight mass spectrometry. (15th June 2020) - Nolot, Emmanuel; Mazel, Yann; Barnes, Jean‐Paul; Sabbione, Chiara; Navarro, Gabriele; Tempez, Agnes; Legendre, Sébastien
Abstract : We demonstrate the potential of using plasma profiling time‐of‐flight mass spectrometry (PP‐TOFMS) to accelerate process developments for phase‐change random access memory (PCRAM) applications, which require advanced materials with composition‐driven properties. We assess the performances of PP‐TOFMS for the chemical depth‐profiling of GeSbTe phase change materials, first after deposition steps to investigate the top surface layer and the incorporation of silicon into the amorphous matrix, then after the thermal annealing step to refine in situ capping strategies, and finally in close loop with etching process steps. Comparison of reference‐free semiquantitative PP‐TOFMS analysis based on ion beam ratio with Rutherford backscattering spectrometry shows remarkable agreement ( 10% relative). PP‐TOFMS proves to be a fast screening tool, which allows process monitoring and selection of samples that indeed need more complex analysis.